2017
DOI: 10.1177/2165079917703410
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Protection Program Compliance in Iranian Hospitals: Application of Fuzzy Analytical Hierarchy Process

Abstract: In hospitals, health care workers (HCWs) are exposed to a wide range of respiratory hazards, which requires using respiratory protective equipment and implementing Respiratory Protection Programs (RPPs). The aim of this cross-sectional study was to investigate RPP implementation in 36 teaching hospitals located in the Fars province of Iran. A researcher-developed checklist, including nine components of the RPP standard, was completed by industrial hygienists in the study hospitals. The Fuzzy Analytical Hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…This may impute to the fact that married health practitioners have the desire and willingness to take part in carrying out the preventive measures because they have spouses and children to protect other than themselves and their clients. This finding is in concordance with the study of Honarbakhsh et al [26] which they indicated that marital status is associated with preventive measures regarding respiratory hazards in the workplace. This research finding, however, conflicts with other past studies [15,27] where no significant association between marital status and the inclination to carrying out the preventive measures.…”
Section: Relationship Of Demographic Profiles Tosupporting
confidence: 82%
“…This may impute to the fact that married health practitioners have the desire and willingness to take part in carrying out the preventive measures because they have spouses and children to protect other than themselves and their clients. This finding is in concordance with the study of Honarbakhsh et al [26] which they indicated that marital status is associated with preventive measures regarding respiratory hazards in the workplace. This research finding, however, conflicts with other past studies [15,27] where no significant association between marital status and the inclination to carrying out the preventive measures.…”
Section: Relationship Of Demographic Profiles Tosupporting
confidence: 82%
“…The recommended OHAS implementations for Respiratory Protection Program (RPP) encompass nine components which are "evaluation of respiratory hazards; selection of respiratory protective equipment (RPE); medical evaluation; fit testing; training; use of RPE; inspection, cleaning, and maintenance of RPE; program evaluation; and recordkeeping." (10). Now the rapid economic growth in developed and developing countries has produced a paradigm shift in occupational health; due to the construction of the vast industrial sector, which introduced a deluge of work-related silica and asbestos (11,13).…”
Section: Respiratorymentioning
confidence: 99%
“…Other influential factors in not using respirators—inaccessibility to respirator and no one does it—were related to managerial issues and should be considered by training and administrative measures including full implementation of a respiratory protection program …”
Section: Discussionmentioning
confidence: 99%